POLITIK HUKUM SEBAGAI ALAT PERLINDUNGAN MASYARAKAT: ANALISIS HUMANIORA TERHADAP SISTEM HUKUM DI INDONESIA - Yusfiansyah, Sofhuan; Wajdu, Fajar (Jurnal AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2025)
This study aims to explore the legal politics of societal protection tools, specifically analyzing the Indonesian legal system from a humanities perspective. The focus lies on the role of legal instruments in safeguarding citizens' rights and their implementation within the framework of Indonesian law. By examining historical, cultural, and social contexts, this analysis investigates how the legal system in Indonesia influences public protection policies, especially in addressing challenges such as human rights violations, social justice, and the balance between state authority and individual freedoms. Utilizing a humanistic approach, this paper highlights the critical need for reforms that can create a more inclusive, fair, and effective legal structure for society. Additionally, the study stresses the importance of legal education and advocacy in raising public awareness of legal protections and ensuring that laws remain aligned with the evolving needs and values of Indonesian society. This research is significant in shaping future legal reforms for better societal protection.